Risk Analysis Using HOR and SWOT on Spice Importers Based on Organization and Industrial Taxonomy - Moh Fuad Firdaus; Wahyuni, Hana Catur (Tibuana, 2021)
Abstract — CV. 777 is a spice import company that has problems in mitigating events that are quite detrimental to the company. Starting from late arrival until over stock in the warehouse. The method used is the House Of Risk and SWOT methods, where with these methods the highest risk can be known and mitigation actions will be taken. This research resulted in 14 Risk Events and 27 Risk Agents where the Risk Agent with the highest ARP value will be followed up using the SWOT method. In the study, one Risk Agent with the highest ARP value or the one with the strongest influence was found, namely Risk Agent A12 with an ARP value of 255 (fluctuations in demand for goods by customers), while the Risk Agent with the weakest influence was A4 with an ARP value of 3 (imported goods). excessive) and A26 with an ARP value of 3 (miscommunication between employees). The risk agent with the highest ARP then continued using the SWOT method and resulted in four strategies, namely SO strategy, ST strategy, WO strategy, and WT strategy. With the mitigation strategy produced by the company, it will be able to minimize the risks that can occur to the company.